Carbonic Acid Pretreatment of Biomass - Walsum, G. Peter van; Jayawardhana, Kemantha; Yourchisin, Damon; McWilliams, Robert; Castleberry, Vanessa (Bayor University, 2003)
This project sought to address six objectives, outlined below. The objectives were met through the completion of ten tasks. 1) Solidify the theoretical understanding of the binary CO2/H2O system at reaction temperatures and pressures. The thermodynamics of pH prediction have been improved to include a more rigorous treatment of non-ideal gas phases. However it was found that experimental attempts to confirm theoretical pH predictions were still off by a factor of about 1.8 pH units. Arrhenius experiments were carried out and the activation energy for carbonic acid appears to be substantially similar to sulfuric acid. Titration experiments have not yet confirmed or quantified the buffering or acid suppression effects of carbonic acid on biomass. 2) Modify the carbonic acid pretreatment severity function to include the effect of endogenous acid formation and carbonate buffering, if necessary. It was found that the existing severity functions serve adequately to account for endogenous acid production and carbonate effects. 3) Quantify the production of soluble carbohydrates at different reaction conditions and severity. Results show that carbonic acid has little effect on increasing soluble carbohydrate concentrations for pretreated aspen wood, compared to pretreatment with water alone. This appears to be connected to the release of endogenous acids by the substrate. A less acidic substrate such as corn stover would derive benefit from the use of carbonic acid. 4) Quantify the production of microbial inhibitors at selected reaction conditions and severity. It was found that the release of inhibitors was correlated to reaction severity and that carbonic acid did not appear to increase or decrease inhibition compared to pretreatment with water alone. 5) Assess the reactivity to enzymatic hydrolysis of material pretreated at selected reaction conditions and severity. Enzymatic hydrolysis rates increased with severity, but no advantage was detected for the use of carbonic acid compared to water alone. 6) Determine ...